Surgical Hyperspectral imaging and Indocyanine green Near-infrared Examination (SHINE) for brain arteriovenous malformation resection: a case report on how to visualize perfusion - Wach, Johannes; Weber, Ferdinand; Vychopen, Martin; Arlt, Felix; Pfahl, Annekatrin; Köhler, Hannes; Melzer, Andreas; Güresir, Erdem (Frontiers in Surgery, 2024)
Background and importanceArteriovenous malformations (AVMs) are complex vascular anomalies that pose significant risks, including intracranial hemorrhage and neurological deficits. Surgical resection is the preferred treatment, requiring precise intraoperative imaging to ensure complete removal while preserving critical structures. This case report presents the first combined use of hyperspectral imaging (HSI) and indocyanine green video angiography (ICG VA) to visualize perfusion during brain AVM surgery, highlighting the potential benefits of these advanced imaging techniques.Case descriptionA 66-year-old male presented with chronic headaches but no neurological deficits. MRI revealed a superficial AVM in the left frontal lobe within the superior frontal sulcus, measuring approximately 2.4 cm. The AVM was fed by feeders from the pericallosal artery, callosomarginal artery, and middle cerebral artery (MCA) branches, with drainage through a dilated cortical vein into the superior sagittal sinus. Preoperative embolization of two MCA feeding branches was performed, followed by microsurgical resection with ICG VA and HSI.ConclusionsThis case report demonstrates the successful application of HSI and ICG VA in brain AVM surgery. The combined use of these technologies provided comprehensive intraoperative assessment, enhancing surgical precision and safety. The integration of HSI offers non-invasive, contrast-agent-free imaging, potentially improving outcomes by enabling detailed perfusion mapping. Future studies should explore the broader applications of these imaging modalities in neurovascular practice.